2010
DOI: 10.1158/1055-9965.epi-09-1220
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Lymphoid and Myeloid Neoplasms in Elderly Solid-Organ Transplant Recipients

Abstract: Background: By assessing the spectrum of hematologic malignancies associated with solid-organ transplantation in the elderly, we provide information on the pathogenesis of lymphoid and myeloid neoplasms and the clinical manifestations of immunosuppression.Methods: Using data from the U.S. Surveillance, Epidemiology, and End Results Medicare database, we identified 83,016 cases with a hematologic malignancy (age 66-99 years) and 166,057 population-based controls matched to cases by age, sex, and calendar year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 38 publications
2
28
1
Order By: Relevance
“…Additionally, studies have reported that certain infectious agents are associated with risk of specific NHL subtypes, such as human T-cell lymphotropic virus, type I (HTLV-I) with adult T-cell leukemia/lymphoma (15), and Helicobacter pylori with gastric mucosa-associated lymphoid tissue NHL (16), whereas infection with the HIV (17)(18)(19) and hepatitis C virus (20,21) are associated with multiple NHL subtypes. Variation in risk among NHL subtypes also is clearly evident for associations with autoimmune conditions (22), iatrogenic immunodeficiency associated with solid organ transplantation (23)(24)(25), and certain common genetic variants (26)(27)(28)(29)(30)(31). In contrast, cumulative sun exposure appears to affect the risk of all NHL subtypes (32).…”
mentioning
confidence: 99%
“…Additionally, studies have reported that certain infectious agents are associated with risk of specific NHL subtypes, such as human T-cell lymphotropic virus, type I (HTLV-I) with adult T-cell leukemia/lymphoma (15), and Helicobacter pylori with gastric mucosa-associated lymphoid tissue NHL (16), whereas infection with the HIV (17)(18)(19) and hepatitis C virus (20,21) are associated with multiple NHL subtypes. Variation in risk among NHL subtypes also is clearly evident for associations with autoimmune conditions (22), iatrogenic immunodeficiency associated with solid organ transplantation (23)(24)(25), and certain common genetic variants (26)(27)(28)(29)(30)(31). In contrast, cumulative sun exposure appears to affect the risk of all NHL subtypes (32).…”
mentioning
confidence: 99%
“…Risk of non-Hodgkin lymphoma in transplant recipients is 3-to 21-fold higher than the general population and 120-fold higher in children who receive transplants. 3 In our series, most malignancies were categorized as PTLD, which typically occurs with advanced disease and frequent extranodal involvement. 4 Our previous study showed that 33% patients were diagnosed with nodal PTLD.…”
Section: Discussionmentioning
confidence: 77%
“…In 2 previous studies that evaluated the risk of non-Hodgkin lymphoma in transplant recipients, there was an increased risk of diffuse large B-cell lymphoma compared with the general population but no increase in follicular lymphoma. 13,14 The risk of lymphoma subtypes may differ by the type of organ transplanted. The risk of developing diffuse large B-cell lymphoma and anaplastic large-cell lymphoma may be greatest in pancreas and in combined kidney and pancreas recipients, but the risk of developing Burkitt lymphoma may be greatest in liver and thoracic organ recipients.…”
Section: Discussionmentioning
confidence: 99%